2022
DOI: 10.3389/fmolb.2022.808162
|View full text |Cite|
|
Sign up to set email alerts
|

6-Shogaol Inhibits Oxidative Stress-Induced Rat Vascular Smooth Muscle Cell Apoptosis by Regulating OXR1-p53 Axis

Abstract: Apoptosis of vascular smooth muscle cells (VSMCs) is closely related to the pathogenesis of cardiovascular diseases, and oxidative stress is an important cause of VSMCs’ death. Inhibiting VSMCs apoptosis is an effective preventive strategy in slowing down the development of cardiovascular disease, especially for atherosclerosis. In this study, we found that oxidation resistance protein 1 (OXR1), a crucial participator for responding to oxidative stress, could modulate the expression of p53, the key regulator o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(64 reference statements)
0
3
0
Order By: Relevance
“…The interplay between apoptosis and necroptosis established a complex network of cell death pathways, collectively influencing the progression and severity of NASH [ 5 , 25 ]. Given the documented anti-apoptotic and anti-necroptotic effects of 6-shogaol [ 10 , 48 ], our study investigated its impact on apoptosis and necroptosis in MCD-diet-fed mice. As expected, mice exposed to the MCD diet exhibited increased apoptosis and necroptosis in the liver, as evidenced by reduced TUNEL-stained apoptotic cells and altered expression of apoptosis- and necroptosis-related molecules.…”
Section: Discussionmentioning
confidence: 99%
“…The interplay between apoptosis and necroptosis established a complex network of cell death pathways, collectively influencing the progression and severity of NASH [ 5 , 25 ]. Given the documented anti-apoptotic and anti-necroptotic effects of 6-shogaol [ 10 , 48 ], our study investigated its impact on apoptosis and necroptosis in MCD-diet-fed mice. As expected, mice exposed to the MCD diet exhibited increased apoptosis and necroptosis in the liver, as evidenced by reduced TUNEL-stained apoptotic cells and altered expression of apoptosis- and necroptosis-related molecules.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ability to remove ROS was enhanced, and the damages caused by oxidative stress were Frontiers in Pharmacology frontiersin.org 16 alleviated. Oxidative stress, a critical part of the cell damage process, has been identified as a core element in cell apoptosis (Liang et al, 2022b;Liu et al, 2022). Meanwhile, oxidative stress-induced apoptosis is closely connected with the p53 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…52 6-Shogaol protects vascular smooth muscle cells from oxidative stress-induced apoptosis by effectively inhibiting p53 activation and preventing upregulation of OXR1 expression. 52 The anti-ageing mechanism of 6-shogaol involves increasing stress resistance through enzyme induction. Lee et al 53 found that in Caenorhabditis elegans , 6-shogaol increased the activity of the antioxidant enzymes SOD and catalase, and also increased the expression of factors of oxidative stress resistance (SOD-3) and heat-shock stress resistance (HSP-16.2), delaying the ageing process.…”
Section: Antioxidant Effects Of 6-shogaolmentioning
confidence: 99%
“…6-Shogaol inhibits overexpression of OXR1 and p53 axes to protect cells from oxidative stress-induced apoptosis. 52 6-Shogaol protects vascular smooth muscle cells from oxidative stress-induced apoptosis by effectively inhibiting p53 activation and preventing upregulation of OXR1 expression. 52 The anti-ageing mechanism of 6-shogaol involves increasing stress resistance through enzyme induction.…”
Section: Food and Function Reviewmentioning
confidence: 99%